2021
DOI: 10.1530/eje-20-1123
|View full text |Cite
|
Sign up to set email alerts
|

Opposing effects of thyroid hormones on cancer risk: a population-based study

Abstract: Objective: The association between dysregulated thyroid hormone function and cancer risk is inconclusive, especially among different age groups and uncommon malignancies. We sought to determine the relation of TSH and free T4 levels with overall cancer risk as well as risk of specific cancer types. Design and methods: Data on thyroid hormone profile was collected from 375,635 Israeli patients with no prior history of cancer. Cancer cases were identified via the Israel National Cancer Registry. Cox proportion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…T3 is an important regulator of androgen signaling, and more specific studies must be performed to discriminate between androgen-dependent and independent mechanisms. TH effects on cancer progression seem to be divergent and depend on the tumoral environment ( 51 , 75 ). As previously reviewed, THs exert dual actions.…”
Section: General Discussion and Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…T3 is an important regulator of androgen signaling, and more specific studies must be performed to discriminate between androgen-dependent and independent mechanisms. TH effects on cancer progression seem to be divergent and depend on the tumoral environment ( 51 , 75 ). As previously reviewed, THs exert dual actions.…”
Section: General Discussion and Perspectivesmentioning
confidence: 99%
“…There is evidence that subclinical or overall hypothyroidism does not modify the risk of prostate cancer, while hyperthyroidism or reduced levels of TSH significantly increase this risk when these parameters are age-adjusted and with any other potential confounder factor [reviews: ( 50 , 51 , 52 , 53 , 54 )]. A prospective study (326 cases/9981 patients) showed that subclinical and frank hypothyroidisms are not associated with cancer risk ( 50 ).…”
Section: Biological Effects Of Thyroid Hormonesmentioning
confidence: 99%
“…23808 cases of cancer were detected over a median follow-up of 10 years. Interestingly, among patients who developed PCa (2,406 over 16,9554 males), elevated TSH levels were associated with decreased risk of PCa, yielding an HR of 0.67 (85). Tran et al found similar data, reporting a significant association between hyperthyroidism and PCa (HR = 1.35) (40) and Mondul et al reported a decreased risk of PCa in men with higher serum TSH compared to men with lower TSH, yielding an Odds Ratio (OR) = 0.70.…”
Section: The Clinical Point Of Viewmentioning
confidence: 99%
“…Among patients aged less than 50 years old at inclusion, TSH levels in the hyperthyroid range, elevated fT4 levels, and subclinical hyperthyroidism were associated with an increased cancer risk (HR, 1.3, 1.28, and 1.31, respectively). Increased TSH levels were correlated with a decreased risk of prostate cancer (HR, 0.67), while log-TSH elevation was associated with an increased risk of melanoma (HR, 1.11) and uterine cancer (HR, 1.27) [ 91 ].…”
Section: Clinical Data On Hypothyroidism As a Potential Predictive Fa...mentioning
confidence: 99%